Pengaruh Strategi Pengembangan Pariwisata terhadap PAD Sektor Pariwisata di Sepuluh Provinsi Destinasi Wisata Prioritas Tahun 2018-2022 - Rahmat, Ervan Nur; Agustina, Neli (Seminar Nasional Official Statistics, 2024)
Tourism is a potential sector to improve the Indonesian economy. The Indonesian government has made efforts to develop tourism by appointing ten priority tourist destinations. However, the contribution of tourism PAD to PAD is still relatively very less. This study aims to analyze the overview of tourism PAD performance and the influence of tourism seen from the 4A components, namely attraction, amenities, access, and ancillary to PAD in ten priority tourist destination provinces. The results showed that Tourism PAD in the provinces of ten priority tourist destinations still fluctuates and has a very insufficient contribution. The estimation results of panel data regression with the Fixed Effect Model show that the number of visitors to tourist attractions, the occupancy rate of star hotel rooms, and the length of the road have a positive influence on PAD. This research is expected to provide information for related parties in determining policies to increase PAD through tourism, especially in the 10 provinces of priority tourist destinations.